Sperm DNA fragmentation and oxidation are independent of malondialdheyde - Gargouri Jalel; Ben Hamida Afifa; Abdallah Fatma; Elleuch Henda; Chakroun Nozha; Zribi Nassira; Fakhfakh Faiza; Keskes Leila (BMC, 2011)
Abstract Background There is clinical evidence to show that sperm DNA damage could be a marker of sperm quality and extensive data exist on the relationship between DNA damage and male fertility status. Detecting such damage in sperm could provide new elements besides semen parameters in diagnosing male infertility. We aimed to assess sperm DNA fragmentation and oxidation and to study the association between these two markers, routine semen parameters and malondialdehyde formation. Methods Semen samples from 55 men attending the Histology-Embryology Laboratory of Sfax Faculty of Medicine, Tunisia, for semen investigations were analysed for sperm DNA fragmentation and oxidation using flow cytometry. The Sperm was also assessed spectrophotometrically for malondialdehyde formation. Results Within the studied group, 21 patients were nonasthenozoospermic (sperm motility ≥ 50%) and 34 patients were considered asthenozoospermic (sperm motility < 50%). A positive correlation was found between sperm DNA fragmentation and oxidation (p = 0.01; r = 0.33). We also found a negative correlation between sperm DNA fragmentation and some sperm parameters: total motility (p = 0.001; r = -0.43), rapid progressive motility (type a motility) (p = 0.04; r = -0.27), slow progressive motility (type b motility) (p = 0.03; r = -0.28), and vitality (p < 0.001; r = -0.65). Sperm DNA fragmentation was positively correlated with coiled tail (p = 0.01; r = 0.34). The two parameters that were found to be correlated with oxidative DNA damage were leucocytes concentrations (p = 0.01; r = 0.38) and broken neck (p = 0.02; r = 0.29). Sperm MDA levels were negatively correlated with sperm concentration (p < 0.001; r = -0.57), total motility (p = 0.01; r = -0.35) and type a motility (p = 0.03; r = -0.32); but not correlated with DNA fragmentation and DNA oxidation. Conclusions Our results support the evidence that oxidative stress plays a key role in inducing DNA damage; but nuclear alterations and malondialdehyde don't seem to be synchronous.